Comparative effectiveness of motivation phase intervention components for use with smokers unwilling to quit: a factorial screening experiment. (19th November 2015) - Cook, Jessica W.; Collins, Linda M.; Fiore, Michael C.; Smith, Stevens S.; Fraser, David; Bolt, Daniel M.; Baker, Timothy B.; Piper, Megan E.; Schlam, Tanya R.; Jorenby, Douglas; Loh, Wei‐Yin; Mermelstein, Robin
Abstract: Aims: To screen promising intervention components designed to reduce smoking and promote abstinence in smokers initially unwilling to quit. Design: A balanced, four‐factor, randomized factorial experiment. Setting: Eleven primary care clinics in southern Wisconsin, USA. Participants: A total of 517 adult smokers (63.4% women, 91.1% white) recruited during primary care visits who were willing to reduce their smoking but not quit. Interventions: Four factors contrasted intervention components designed to reduce smoking and promote abstinence: (1) nicotine patch versus none; (2) nicotine gum versus none; (3) motivational interviewing (MI) versus none; and (4) behavioral reduction counseling (BR) versus none. Participants could request cessation treatment at any point during the study. Measurements: The primary outcome was percentage change in cigarettes smoked per day at 26 weeks post‐study enrollment; the secondary outcomes were percentage change at 12 weeks and point‐prevalence abstinence at 12 and 26 weeks post‐study enrollment. Findings: There were few main effects, but a significant four‐way interaction at 26 weeks post‐study enrollment ( P  = 0.01, β = 0.12) revealed relatively large smoking reductions by two component combinations: nicotine gum combined with BR and BR combined with MI. Further, BR improved 12‐week abstinence rates ( P  = 0.04), and nicotine gum, when used without MI, increased 26–week abstinence after a subsequent aided quit attempt ( P  = 0.01). Conclusions: Motivation‐phase nicotine gum and behavioral reduction counseling are promising intervention components for smokers who are initially unwilling to quit.